Gender-Sensitive Sex Education for Boys* - Gottfried Schweiger (Sexes)
Sex education goes far beyond merely conveying biological facts; it encompasses the psychological, social, and cultural aspects of sexuality. A gender-sensitive approach to sex education for boys* aims to address their specific needs and challenges, critically reflect on hegemonic norms of masculinity, and develop alternative, non-toxic models of masculinity. This article explores the foundations and core elements of such a gender-sensitive sex education for boys*, considering theoretical concepts such as sexual socialization, hegemonic masculinity, and sexual scripts, as well as sexual health and rights for boys*. An intersectional perspective enables a nuanced analysis of the diverse social inequalities that shape boys’* sexual development. This paper argues for four key elements of gender-sensitive sex education for boys*: (1) empowerment and self-determination to strengthen boys* in their formation of sexual identity; (2) the development of alternative masculinities to challenge stereotypical gender constraints; (3) the promotion of gender justice by raising boys’* awareness of their societal responsibility; and (4) fostering critical competencies in dealing with media and social norms. These approaches contribute to establishing a holistic and inclusive form of sex education that acknowledges boys* in their diversity and helps create a more just society.